2020
DOI: 10.3389/fonc.2020.590033
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition to Solid Pediatric Cancers

Abstract: Progresses over the past years have extensively improved our capacity to use genome-scale analyses-including high-density genotyping and exome and genome sequencing-to identify the genetic basis of pediatric tumors. In particular, exome sequencing has contributed to the evidence that about 10% of children and adolescents with tumors have germline genetic variants associated with cancer predisposition. In this review, we provide an overview of genetic variations predisposing to solid pediatric tumors (medullobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 286 publications
0
26
0
1
Order By: Relevance
“…Several genes related to predisposition to different childhood malignancies have been described since then (myeloid leukemia [ 8 ] and lymphoblastic leukemia [ 9 ], neuroblastoma [ 10 ], medulloblastoma [ 11 , 12 , 13 ], osteosarcoma [ 14 ] and soft tissue and bone sarcomas [ 15 , 16 ]). Meanwhile, knowledge on several disorders remains scarce, but current next generation sequencing technologies have expanded the frontiers of genetic predisposition research and, hence, the possibility of discovering new genotype–phenotype relationships [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several genes related to predisposition to different childhood malignancies have been described since then (myeloid leukemia [ 8 ] and lymphoblastic leukemia [ 9 ], neuroblastoma [ 10 ], medulloblastoma [ 11 , 12 , 13 ], osteosarcoma [ 14 ] and soft tissue and bone sarcomas [ 15 , 16 ]). Meanwhile, knowledge on several disorders remains scarce, but current next generation sequencing technologies have expanded the frontiers of genetic predisposition research and, hence, the possibility of discovering new genotype–phenotype relationships [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Germline mutations have been detected in 8-18% of children and adolescents with cancer [3,[8][9][10], and the most prevalent CPGs reported to be mutated are TP53, APC, BRCA2, NF1, PMS2, RB1, andRUNX1 [3]. In a very recent work about the spectrum of germline mutations in childhood cancer, the majority of the mutations (55%) were mapped to genes not previously associated with the patient's tumor type [10]; this work included a small number of HB patients (3 patients) with no pathogenic or likely pathogenic variants.…”
Section: Discussionmentioning
confidence: 99%
“…Most investigations have focused on known CPGs and sequenced patients without parental samples, an approach that impairs a broad evaluation of the full range of genetic mechanisms underlying pediatric cancer risk, such as de novo mutations and the identification of new candidate CPGs. Recent studies of large cohorts of pediatric cancer patients have confirmed that approximately 8-18% of patients carry a germline pathogenic variant in a broad spectrum of known CPGs [3,[5][6][7][8][9][10]. These studies also highlighted that isolated factors, such as tumor type and a positive family history of cancer, have low predictive power for the presence of germline CPG mutations.…”
Section: Introductionmentioning
confidence: 99%
“…CPS are defined by their canonical germline mutations, but also by the phenotype(s) of their associated neoplasms 197 . Each of the mutated genes with the end result of a clinical malignancy of one type or another has set molecular perturbations such as disordered genomic stability and cell cycle dysregulation as in the case of LFS [TP53] or miRNA processing in the DICER1 syndrome 198 , 199 .…”
Section: Commentary/conclusionmentioning
confidence: 99%